Convenient formal synthesis of (+/-)-paroxetine - Chavan, Subhash P.; Khobragade, Dushant A.; Pathak, Ashok B.; Kalkote, Uttam R. (Synthetic Communications, 2007)
A formal total synthesis of antidepressant (+/-)-paroxetine employing a solvent-free Heck reaction is disclosed.
Keywords: antidepressants; carbamate; electrophile; Heck reaction; piperidines

Practical formal synthesis of camptothecin - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Tetrahedron Letter, 2007)
The synthesis of the DE ring of camptothecin using simple and inexpensive starting materials, employing an addition elimination reaction and selective esterification of an aliphatic carboxylic acid as key steps is described. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: alkaloid; Anticancer; camptothecin; Natural product

Short and efficient synthesis of rubrolide E - Chavan, Subhash P.; Pathak, Ashok B.; Pandey, Ankur; Kalkote, Uttam R. (Synthetic Communications, 2007)
Short and efficient synthesis of rubrolide E from commercially available 4-methoxyacetophenone, employing ring-closing metathesis, Knoevenagel condensation, and Reformatsky reactions, are the key steps are described.
Keywords: antibiotics; antitumor; Epoxide; Natural products; Total synthesis

Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Total synthesis of pulchellalactam via an RCM strategy - Chavan, Subhash P.; Pathak, Ashok B.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthetic Communications, 2007)
Total synthesis of (Z) pulchellalactam, a CD protein tyrosine phosphatase inhibitor, from commercially available methallyl chloride employing ring-closure metathesis (RCM) as a key step is described.
Keywords: alkaloid; Natural products; pulchellalactam; RCM; Total synthesis

Synthesis of 3-ethyl-4-metyl-1h,5-dihydro-2h-pyrrol-2-one by novel palladium(ii)-catalyzed cyclization and ring-closing metathesis - Chavan, Subhash P.; Pathak, Ashok B.; Pawar, Kailash P. (Synthesis-Stuttgart, 2015)
Synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one is described starting from commercially available allylamine and 4-methoxybenzylamine employing palladium-catalyzed cyclization or ring-closing metathesis as the key steps.
Keywords: antidiabetic; cyclization; glimepiride; lactams; metabolite; pyrrolinone; Ring-closing metathesis